The Law of Movasat and the Moral Challenge of Staying at Home During the COVID-19 Pandemic - Shiravand, Mohsen; Mirhadi, Zahra Sadat (Al-Jami'ah Research Centre, 2023)
The challenge of the COVID-19 Pandemic is usually reduced to a mere medical and health problem, while one can observe its sizeable influence on economic, cultural, political and moral domains, too. In Muslim countries, moral conflict becomes one of the significant challenges of COVID-19 affecting people’s lives. Staying at home and its relationship with livelihood is one of the most complicated of these conflicts. In this essay, the authors assess and expose this moral conflict using the ethical doctrines of the Islamic religion rooted in the moral law of Movasat Altruism. There are four strategies in the principle of Movasat for overcoming the crisis: (1) uprooting poverty and reducing social-economic inequality; (2) job creation and supporting the production cycle; (3) eliminating unnecessary brokers; and (4) strengthening sympathy, empathy, and love within society.[Tantangan akibat Pandemi COVID-19 banyak difokuskan hanya sebatas masalah medis dan kesehatan saja, padahal pengaruhnya juga terlihat cukup besar dalam bidang ekonomi, budaya, politik, dan moral. Di negara-negara Muslim, konflik moral menjadi salah satu tantangan signifikan akibat COVID-19 yang berdampak pada kehidupan masyarakat. Tinggal di rumah dan hubungannya dengan penghidupan merupakan contoh salah satu konflik yang cukup rumit. Dalam tulisan ini, penulis berupaya mengungkap konflik moral ini dengan menggunakan doktrin etika agama Islam yang berakar pada hukum moral altruisme Movasat. Ada empat strategi dalam prinsip Movasat untuk mengatasi krisis: (1) memberantas kemiskinan dan mengurangi kesenjangan sosial ekonomi; (2) menciptakan lapangan kerja dan mendukung siklus produksi; (3) menghilangkan perantara yang tidak diperlukan; dan (4) memperkuat simpati, empati, dan rasa cinta kasih dalam masyarakat.]